Phytochemical Screening and Comparative Antioxidant Activity of Eclipta alba (L.) Leaf Extracts: Research Article (Journal of Pharma Insights and Research, 2026)
Eclipta alba (L.) which belongs to the Asteraceae family is widely used in Ayurvedic and Siddha medicine due to its therapeutic efficacy in treating hepatic disorders, skin ailments, and respiratory conditions. The therapeutic potential of this herb is primarily attributed to a diverse array of secondary metabolites, including coumestans, flavonoids, and phenolic acids. This study involved a comparative analysis of phytochemical constituents and antioxidant activities across leaf extracts obtained through petroleum ether, acetone, and ethanol using a cold percolation method. Quantitative spectrophotometric assays revealed that while the ethanolic extract provided the highest percentage yield (3.264%), the petroleum ether extract exhibited the most potent antioxidant activity with the lowest EC₅₀ value (0.872 mg/mL) and the highest Antioxidant Radical Power (ARP). Total phenolic and flavonoid contents were significantly higher in the petroleum ether and acetone extracts compared to the ethanolic fraction, suggesting that the antioxidant efficacy is closely linked to the concentration of these bioactive molecules. Thin Layer Chromatography (TLC) confirmed the presence of wedelolactone, a marker bioactive compound, across the extracts. The findings establish that solvent polarity significantly influences the extraction efficiency and biological potency of E. alba. The robust radical scavenging activity observed supports the traditional application of the plant as a natural hepatoprotective and anti-aging agent, providing a scientific basis for its integration into modern antioxidant-based therapeutic regimens